Complications and adverse events of plaque brachytherapy for ocular melanoma - Peddada, Krishi; Sangani, Roshun; Menon, Hari; Verma, Vivek (Journal of Contemporary Brachytherapy, 2019)
Plaque brachytherapy is a well-accepted modality to manage selected cases of ocular melanoma. Although this modality provides validated oncologic and quality of life benefits, severe complications and adverse events can occur. This article reviews complications and adverse events of plaque brachytherapy, including scleral necrosis, strabismus, cataract, glaucoma, and retinopathies as well as management of these conditions. For practicing oncologists and ophthalmologists, these complications are important to understand, identify, and treat. Additionally, an understanding of common complications of brachytherapy should influence the decision of pursuing it as a treatment option.